Comparison of the effect of iguratimod and hydroxychloroquine on regulatory B cells in the treatment of primary Sjögren’s syndrome - Zou, Jin-Mei; Yang, Li; Luo, Jia-Ang; Ren, Yan; Li, Si-Yin; Zhang, Yu; Dong, Jian-Ling; Deng, Dai-Hua; Ni, Yuan-Piao; Li, Min; Yin, Xiao-Shuang; Yang, Jing (Frontiers in Medicine, 2025)
ObjectivesThis study aimed to evaluate the efficacy of iguratimod (IGU) and hydroxychloroquine (HCQ) in the treatment of primary Sjögren’s syndrome (pSS).MethodsThis was a randomised controlled study. A total of 60 patients with pSS in Mianyang Central Hospital were recruited between December 2020 and December 2022. They were randomly divided into two groups: the IGU group and the HCQ group. Treatment in the IGU group was as follows: ≤10 mg of prednisone per day, 25 mg of IGU twice a day; treatment in the HCQ group was as follows: ≤10 mg of prednisone per day, 0.2 g of HCQ twice a day. The EULAR Sjögren’s Syndrome Disease Activity Index (ESSDAI) and the European League against Desiccation Sjögren’s Syndrome Patient Reported Index (ESSPRI) were used to assess disease activity.ResultsAfter 6 months of treatment, the levels of immunoglobulin G (IgG) and ESSPRI in the IGU group were significantly lower than those in the HCQ group and the levels of CD19+CD5+CD1d+ B cells were significantly higher than those in the HCQ group (p < 0.05). Compared with baseline, the serum IgG level, erythrocyte sedimentation rate (ESR), B lymphocytes, ESSDAI, ESSPRI and Functional Assessment of Chronic Illness Therapy (FACIT) were significantly decreased and CD19+CD5+CD1d+ B cells were significantly increased in the IGU group after 6 months of treatment. In the HCQ group, C-reactive protein, ESR, ESSDAI, ESSPRI and FACIT were significantly decreased; there was no significant difference in regulatory B cells before and after treatment.ConclusionBoth IGU and HCQ can reduce the disease activity and fatigue score of patients with pSS. However, IGU was superior to HCQ in reducing IgG levels. Furthermore, IGU can affect the levels of peripheral blood B lymphocytes and CD19+CD5+CD1d+ B cells.